Характеристика питания птенцов некоторых видов насекомоядных синантропных птиц - Смогоржевский, Л.А.; Коткова, Л.И. (Вестник зоологии, 1973)
When studying the nestlings nutrition Hirundo rustica L. (25 tests), Delichon urbica L. (54 tests), Motacilla alba L. (33 tests) and Muscicapa striata (P a I I.) (44 tests), 23, 59, 19, 38 species or groups of food objects were detected respectively. Such variability of nutrition objects permits these bird:1 quickly switch over to other more available food in case of necessity.